HUBUNGAN ANTARA KADAR TIMAH (Pb) HITAM DALAM DARAH DENGAN KADAR HEMOGLOBIN (Hb) (The Relationship Of Blood Lead Leveland Hemoglobin Level) - -, saifudin zukhri; -, Bambang Soempeno; -, Doeljacman Moeljohardjo Moeljohardjo (MOTORIK Jurnal Ilmu Kesehatan (Journal of Health Science), 2007)
The increased number of motor vehicles which not balace by widing or prolonging of road will accumulate emission on the air. One of the emission component was lead (Pb). Some researchs indicated that had negative effects to health. This study was aimed to know the relationship between blood lead level and hemoglobin level of the street boys in Yogyakarta. This was an analytical observasional (non experimental) research with cross sectional study. The subjects of this study were 30 street boys (10-18 years old) which resided in special cross roads of main road in Yogyakarta, i.e.Malioboro (post office), PKU Muhammadiyah Hospital, Gramedia Book Store and Mirota Campus. Two milliliters of blood were drawn up from the cubital vein of the subject to examine the blood lead level (ug/dl) with Atomic Absorbent Spectrophotometry, and to examine the hemoglobin level (g/dl) with cyanmethemoglobin metode by microlab spectrophotometry 300. There were only 26 of 30 subjects which fulfilled the criterions to be analyzed. Data were analyzed by Spearman’s Rho correlation test and multiple regression. A p value af d”0,05 was set as a significant level. The result showed that the average of streer boy’s blood lead level were 150,8 ± 41,20 ug/dl. All of the street boys had the blood lead level more than 10 ud/dl (the blood leadlevel threshold for children was defined by ATSDR). The average of hemoglobin level of the street boys were 10,28 ± 1,51 g/dl, which 70,08 % of them suffered anemia (hemoglobin level <12g/dl). Bivariate Spearman’s Rho correlations test result demontrated thatblood lead level and history of alcohol intake had negative correlation with the hemoglobin level (r = -0,663 and -0,396 respectively). Age,nutrition status, smoking habit, and expose duration had no correlation significantly with the hemoglobin level. Multiple regression test result showed that blood lead level was the only factor that predict the hemoglobin level. Contributions of blood leaf level were 36,7 % toward hemoglobin level, so the contributions of other factory that influenced hemoglobin level were 63,3 %. Increased of  1 ug/dl of blood lead level was responsible to 0,22 g/dl decreased of hemoglobin level. It was concluded that blood lead level had negative linier correlation with the hemoglobin level.   Key word : lead, hemoglobin, anemia